Knowledge by stipulation: the rectification of names - Shahab, Syed Alwi (INSTED, IIUM Prees, 2009)
A lot of what we claim to know, in current discussions of knowledge, the knowledge society, the knowledge economy and the knowledge industry such as have very little to do with knowledge and knowing in the putative sense. The creation of knowledge starts with belief, and only when belief has been converted into a known- by direct experience and encounter, among other things-does it finally coalesce into knowledge. You have to walk through an experience, traverse it, survive it (in a manner of speaking) before you can finally own it. A known becomes an experience that you own, and this, in the true sense of the word is what you can honestly describe as having knowledge of something. The possibility of a collectively shared known is not entirely ruled out-but this will be more in the sense of a pastiche or mosaic of a variety of unique individual knowns sharing a family resemblance in the Wittgensteinian sense. So what is left over from all this will be "raw" beliefs which have not been converted into knowns and other synthetic or hybrid simulcra commonly seen as information or data.